TMOD-03. PAN-CANCER ANALYSIS OF ORTHOTOPIC PATIENT DERIVED XENOGRAFTS FROM BRAIN METASTASES. (9th November 2020) - Zeng, Yu; Pelton, Kristine; Yerrum, Smitha; Kao, Pei-Lun; Sinai, Claire; Tran, Tony; Sinha, Rileen; Shetty, Aniket; Tolstorukov, Michael; Jaber, Aliya; Freitas, Dylan; Pisano, William; et al.
Abstract: Brain metastases (BM) are a leading cause of cancer death and prognosis remains poor despite treatment advances at other sites. Models are central to therapeutic development, but few orthotopic patient-derived xenograft (PDX) models of BM exist. To represent diversity across BM types, we established a program to create orthotopic PDX at scale from all BM patients. To date BM were received from 100 patients and PDX attempted by direct brain injection (PDX, n=89) or injection of low passage patient-derived cell lines (PDCLX, n=11). We created 65 successful BM PDX from 13 cancers: 17 lung (55% take), 15 breast (68%), 6 melanoma (75%), 5 CNS lymphoma (83%), 3 gastrointestinal (75%), 2 esophageal (40%), 2 ovarian (67%), 1 sarcoma (100%), 1 laryngeal (100%), 1 prostate (100%), 1 pancreatic (100%), 1 uterine adenosarcoma (100%), and 1 yolk sac tumor (100%). Take rate was similar for models derived from patients with prior chemotherapy-only versus immune/targeted therapy-only (63 vs 58%). Fifteen patients had live tumor and matching PBMCs archived for modeling in vitro immunotherapy responses. Mean time to moribund among different cancer types ranged from 27 days (yolk sac tumor) to 177.5 days (ovarian). BM PDX had a favorable timeline for preclinical study (90% moribund at 180 days). All PDX retained high fidelity to the patient driver SNVs and copy aberrations, even at >P4. No significant differences noted by immunodeficient strain (SCID versus NSG) or injection site (orthotopic versus heterotopic). Explants from BM PDX were able to generate long-term cell lines (60%) or short-term cultures with qualitative concordance of model-to-patient responses to targeted therapy (Osimertinib, EGFRi) and immunotherapy (Pembrolizumab, PD1i). Genomic and clinical data were used to create the DFCI BM PDX cBioPortal for public release and models distribution will be available through the DFCI Center for Patient Derived Models.